Technical Study of Ship Plate Firing Process Time with Variation of Deformation Values - Widiyanto, Sinung; Hardianto, Didik; Kristiyono, Tri Agung; Aditya, Bagus Kusuma; Rifandi, Safriudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
In the process of shipbuilding production and repair, deformation is sometimes encountered due to several factors, starting from load pressure, pulling, lifting, and welding processes. A fairing process is carried out to overcome the plate deformation, in which the plate is heated and cooled simultaneously. The method used in this research is direct time measurement during the fairing process on test plate specimens with variations in the depth of deformation curvature. The data obtained, processed, and analyzed to obtain an estimate of the fairing processing time the longer the fairing process takes, following the equation Y = 41.285X + 530.94, where X is the deformation angle, and Y is the estimation fairing processing time area per half square meter.